Establishment of diuretic activity indicators for (3-thio-4-R-4-H-1,2,4-triazole-5-yl)(phenyl)methanols and their derivatives - A. M. Rud; A. G. Kaplaushenko; Ye. S. Pruglo; Yu. S. Frolova (Zaporozhye State Medical University, 2018)
Diuretic drugs are drugs that, by blocking the transport systems of the renal tubules, promote the removal of excess electrolytes and water from the body, normalization of the internal environment. They eliminate edema, reduce the fluid content in the body cavity. Diuretic drugs differ in their chemical structure, the mechanism of action on the urinary tract function of the kidneys and on the mechanisms of regulation of this function. It should be noted that the use of the above mentioned agents can lead to undesirable side effects, such as nausea, vomiting, unpleasant sensations in the stomach, headache, facial hyperemia. To date, there is evidence that 5-R-1,2,4-triazole derivatives have diuretic activity. The advantage of synthetic triazole derivatives is that, along with the expressed pharmacological action of the compound, there are relatively low rates of acute and chronic toxicity, but almost no side effects. Therefore, it is important to create new low-toxic substances of derivatives (3-thio-4-R-4-H-1,2,4-triazole-3-yl)(phenyl)methanols and study their diuretic properties. The purpose of the work is the purposeful search for new low-toxic and highly effective diuretic compounds among the derivatives of (3-thio-4-R-4-H-1,2,4-triazole-5-yl)(phenyl)methanols. Materials and methods. To establish the influence of compounds, which have been synthesized at the Physical and Chemical Chemistry Department of ZSMU, the method of E. B. Berchin was used on the excretory function of kidneys. Experiments on diuretic activity were conducted at the Department of Clinical Pharmacy, Pharmacotherapy and MFE of FPE, Zaporizhzhia State Medical University. Results. The diuretic activity of derivatives (3-thio-4-R-4H-1,2,4-triazole-5-yl)(phenyl)methanols was investigated. The study and analysis of the obtained experimental data were compared with the reference diuretic hypothiazide. Regularities "structure - activity" were established. The studies indicate that (3-thio-4-R-4H-1,2,4-triazoles-3-yl)(phenyl)methanol are not able to exceed hypothiazide diuretic effect, but 4-(5-hydroxy(phenyl)methyl-4-phenyl-4H-1,2,4-triazolе-3-ylthiomethyl)benzonitrile showed the results closer to the reference drug. Conclusion. By the method of E.B. Berchin the diuretic activity of derivatives (3-thio-4-R-4H-1,2,4-triazol-5-yl)(phenyl)methanols was investigated. Derivatives (3-thio-4-R-4H-1,2,4-triazole-3-yl)(phenyl)methanols do not excee the diuretic action of hypothiazide. Patterns "structure - action" were established. The most active compound was 4-(5-hydroxy(phenyl)methyl-4-phenyl-4H-1,2,4-triazolе-3-ylthiomethyl)benzonitrile.